Розробка вебзастосунку для логістики з розрахунку вартості перевезень та пошуку найкоротших маршрутів - Поляков, В. Д. (ХНУРЕ, 2025)
The paper is devoted to the development of a web application for calculating freight transportation costs and determining the shortest routes. The paper reviews modern approaches to building such platforms with an emphasis on route optimization algorithms, cost calculation methods, integration with mapping services, and real-time tracking features. Particular attention is paid to the challenges of processing large data sets and ensuring the accuracy of distance calculations. A comparative analysis of existing solutions such as Google Maps API, Here Maps, and OpenRouteService highlights their strengths and weaknesses in the context of logistics, but does not take into account costs and cost calculation. In addition, the study considers competing logistics management systems such as PCS Express and Ditat, analyzing their functionality, pricing models, and overall efficiency in freight transportation management. The paper also explores the future potential of integrating artificial intelligence for predictive route planning and dynamic pricing based on traffic conditions and weather events. The results of this work demonstrate the effectiveness of the optimized logistics system and offer ideas for further improvement.
Keywords: вартість перевезень; логістика; пошук найкоротших маршрутів